Continuous Solutions of Integral Equations via Schauder’s Theorem - LAKHAL, Malika (Faculty of Mathematics and computer sciences Department of Mathematics - Option : Mathematical and numerical analysis, 2021)
In this memory, we study and classify integral equations, and focus on Volterra and Fredholm non-linear integral equations. The aim of this paper is to prove the existence of solution of some nonlinear Fredholm and Volterra integral equation, integral equation with Delay in Banach spaces, using Schauder’s fixed point theorem.
Keywords: Fredholm's integral equations, Volterra's integral equations, Schauder's fixed point theorem, Riesz's theorem, integral equation with Delay.